2021
DOI: 10.31763/ijrcs.v1i1.225
|View full text |Cite
|
Sign up to set email alerts
|

The Path Direction Control System for Lanange Jagad Dance Robot Using the MPU6050 Gyroscope Sensor

Abstract: The ability to walk straight on a dance robot is very important considering that in competitions, dance robots are required to be able to walk through several zones starting from the starting zone and ending with the closed zone. Therefore, a control system is needed in the Lanange Jagad dance robot so that the robot can control the direction of its walking motion and reduce errors in dance motion while walking on the dance robot. This control system uses a reading value based on the orientation of the rotatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Nevertheless, thanks to robots' increasingly intelligent humanoid features, robot-expressed dance will soon cause emotional resonance with the audience and influence the audiences' emotional expression. In the process of robot-expressed dance, factors affecting the audience's judgment also have particular research significance (Rifajar and Abdul, 2021 ). The sense of rhythm, the coherence of movement, and the symmetry of movement will affect the effect of dance, which requires reflection and research on the dance art itself.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, thanks to robots' increasingly intelligent humanoid features, robot-expressed dance will soon cause emotional resonance with the audience and influence the audiences' emotional expression. In the process of robot-expressed dance, factors affecting the audience's judgment also have particular research significance (Rifajar and Abdul, 2021 ). The sense of rhythm, the coherence of movement, and the symmetry of movement will affect the effect of dance, which requires reflection and research on the dance art itself.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [21] showed the implementation of IMU for outdoor applications where estimation of absolute attitude is compared with a kinematic model of motion, while Albaghdadi and Ali [22] introduced detailed methods to overcome measurement error caused by vibration when using the MPU6050 module. Jefiza et al [23] and Al-Dahan et al [24] used the MPU6050 module to detect the fall of the elderly when walking, while Rifajar and Fadlil [25] used it to detect the fall of a dancing robot by monitoring the acceleration of rotational motion. The approach to measuring joint angles in this research is different, where the measured orientation is used to calculate joint angles of the DC actuators based on (9).…”
Section: Platform Testing Methodsmentioning
confidence: 99%
“…Microelectromechanical system (MEMS) gyroscopes offer several advantages over other sensors used for the same purpose, highlighting their low cost, high accuracy, ease of integration, and the ability to be manufactured on a large scale [45], [46]. These devices have the potential to be applied in various fields, such as image stabilization [47], movement control of different robots [48]- [51], navigation of unmanned aerial vehicles (UAV) [52], [53], detection of the state of movement of people [54], self-stabilization systems [55], [56], and locating the geographic north [57]. These sensors have been used for various purposes to measure the electrical motor parameters.…”
Section: Introductionmentioning
confidence: 99%